Analisis Beban Kerja Dan Kebutuhan Pegawai pada Unit Kerja Kecamatan Rungkut Kota Surabaya - Oktavia Putri Khoirril; Nawangsari, Ertien Rining (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The existence of a country cannot be separated from the existence of it’s population. Population growth in Indonesia continues to increase from year to year in almost every region. The large population causes problems regarding the fulfillment of rights, needs, protection and public services. In the current era, public services have great demands from the public, the public sector is asked to provide excellent service by showing high professionalism. However, the demands and hopes of the community have not been fully realized. Based on data released by the Central Statistics Agency (2024), in 2015-2023 the number of civil servants in Indonesia continued to decline, this was also a factor causing the workload carried out by each employee to increase. Several factors that hinder public services are part of the Government's regulations regarding Bureaucratic Reform. Bureaucratic reform is a need that needs to be fulfilled in ensuring the creation of good governance. In the Rungkut Subdistrict Work Unit, there are complaints that there are not enough employees to carry out the large workload. With these complaints, the author feels it is necessary to carry out an analysis of the workload in the Rungkut District Work Unit by referring to PermenPANRB No. 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis, so that the results of the workload analysis are expected to provide information regarding the ideal number of employees according to the workload.